The impact of heuristic availability bias on investment decision‐making: Moderated mediation model. Issue 3 (20th October 2020) - Salman, Muhammad; Khan, Bakhtiar; Khan, Sher Zaman; Khan, Rafi Ullah
Abstract: This study tends to examine the moderated mediation role of external locus of control (ELC) and risk tolerance (RT) in the relationship between heuristic availability bias (HAB) and investment decision‐making (IDM). We used SPSS PROCESS Model 7 (moderated mediation) on a data set gleaned from 385 practicing stock investors at Pakistan Stock Exchange. The results of the study revealed that the relationship between HAB and IDM is partially mediated by RT, whereas, the ELC significantly moderates the relationship between HAB and RT. Moreover, in the case of moderated mediation, the ELC showed a significant moderating role in the relationship of HAB with IDM through RT. Since the findings of the study argue that ELC intensifies the influence of HAB on investors' risk‐taking propensity that inculcate them toward making investment decisions. The practical and theoretical implications of the study are discussed in detail.